Abnormal Fractional Flow Reserve in Nonobstructive Coronary Artery Disease: The Relationship With Plaque Characteristics. (February 2019) - Imai, Shunsuke; Kondo, Takeshi; Stone, Gregg W.; Kawase, Yoshiaki; Ahmadi, Amir A.; Narula, Jagat; Matsuo, Hitoshi
Abstract : Background: The basis of discordance between invasive coronary angiographic (ICA) anatomic stenosis and fractional flow reserve (FFR) is not fully understood. We analyzed coronary computed tomography angiography (CTA) characteristics of ICA-verified nonobstructive lesions in the proximal or midleft anterior descending artery with FFR ⩽0.8, that is, anatomy-physiology mismatch. Methods and Results: CTA and ICA were performed in 108 patients. FFR was measured during intravenous ATP (180 μg/[kg·min]) infusion. CTA-verified plaque characteristics between 53 consecutive ICA-FFR mismatch (ICA–quantitative coronary angiography <50%, FFR⩽0.8) and 55 ICA-FFR match (ICA–quantitative coronary angiography<50%, FFR>0.8) vessels were compared. CTA-verified vessel area (20.7±6.7 versus 16.9±4.8 mm 2 ; P =0.0007), positive area remodeling index (ARI; 1.38±0.23 versus 1.06±0.11; P <0.0001), %plaque area (64.7±12.7 versus 57.4±8.5%; P <0.0007), jeopardized myocardial mass (46.2±18.5 versus 37.1±14.3 g; P = 0.006), and the prevalence of low attenuation plaque (45.3% versus 9.1%; P <0.0001) at the minimum lumen area were significantly higher in the ICA-FFR mismatch than the match group. By receiver operation curve analysis, the areas under the curve for positive area remodeling index, %plaque area and jeopardized myocardial mass were 0.921, 0.681, and 0.641, respectively, for the diagnosis of mismatch (cutoff values 1.13, 66% and 58.7 g, respectively). The sensitivity and specificity of area remodeling index >1.13 for predicting ICA-FFR mismatch were 88.7% and 78.2%, respectively. Conclusions: In the absence of anatomically significant stenosis, abnormal FFR is more frequently encountered in patients with CTA-derived positive remodeling, larger plaque burden, and low attenuation plaque. These findings contribute to a better understanding of how FFR-based decision-making might translate into demonstrated superior clinical outcomes.